The bankers how the banks brought Ireland to its knees - Ross, Shane (Penguin Ireland, 2009)
Two years ago, the Irish economy was still booming; now, it faces an unprecedented crisis. There is, of course, an international context for these developments, but the Irish story, a story of collusion between banks, regulators & the government is perhaps unique in its tawdriness. This book tells the story.